Synthesis of MgNiO2/CoNC-Based Ternary Metallic Dual-Active Interfacial Porous Hollow Nanocages as Efficient Oxygen Reduction Reaction and Oxygen Evolution Reaction Bi-Functional Electrocatalysts - Li, Shanshan; Yuan, Yang; Zhang, Qing; Chang, Fangfang; Yang, Lin; Bai, Zhengyu (Frontiers in Materials, 2020)
Combining the catalytic activities of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) into one electrocatalyst is of great significance in simultaneously prompting the charge-discharge cycles of various renewable energy storage and conversion systems such as metal-air batteries. Herein we report a ternary metallic based MgNiO2/CoNC porous hollow nanocage composite, which assembled with intimate contacted MgNiO2 and Co species to form the ultrathin nanocage shells and serve as the ORR and OER active components respectively to reveal a highly bi-functional catalytic performance. The possible synergy of each seamlessly connected metallic sites renders the hybrid material with excellent ORR and OER activities, which outperform than the corresponding benchmarks. Particularly, we speculate such efficient catalytic activity might arise from the synergistic chemical coupling effects within MgNiO2/CoNC and therefore, these results reveals promising prospects in developing multi-metallic composites toward efficient electrochemical energy devices.